COMPARATIVE EFFECTIVENESS OF CARDIOCYTE PROTECTORS IN COMPLEX MANAGEMENT OF ARTERIAL HYPERTENSION - F. E. Khlebodarov; V. P. Mikhin; A. V. Gorlova (Российский кардиологический журнал, 2009)
The study investigated the effects of cardiocyte protectors, mexicor and mildronate, in combination with ACE inhibitors, on blood levels of lipid peroxidation products, vascular endothelial function, circadian profile of blood pressure, and left ventricular morphology and function in patients with arterial hypertension. The results obtained supported the importance of cytoprotectors mexicor and mildronate, combined with ACE inhibitors, in the complex management of arterial hypertension. Compared to mildronate, mexicor more effectively influenced blood levels of lipid peroxidation products, circadian blood pressure profile, and left ventricular diastolic myocardial function.